Heat Transfer Optimization of Series-Wound Space Radiators - XueTao Cheng (Advanced Energy Conversion Materials, 2024)
In spacecraft, the analysis and optimization of space radiators are very important for improving the performance of thermal control system. In this paper, a physical and mathematical model for heat transfer optimization of series-wound space radiators is set up. With the model, a system with five space radiators is optimized to obtain the optimal distributions of total thermal conductance that lead to the maximum heat transfer rate for fixed inlet temperature of the fluid and the minimum inlet temperature of the fluid for fixed heat transfer rate, respectively. The influences of the operation parameters on the optimization results are discussed. When the inlet temperature or the heat transfer rate is fixed, it is shown that the value of total thermal conductance has little effect on the optimal distribution. When the total thermal conductance is fixed, the results show that neither the inlet temperature of the fluid nor the heat transfer rate is an important factor that affects the optimization results. Furthermore, the applicability of the entropy generation minimization and the entransy theory to the analysis of the system is also discussed. Both the theoretical analysis and the numerical results show that the entransy theory is always applicable to the optimization problems, while the entropy generation minimization is not.